Association Studies and Direct DNA Sequencing Implicate Genetic Susceptibility Loci in the Etiology of Nonsyndromic Orofacial Clefts in Sub-Saharan African Populations. (October 2016) - Gowans, L.J.J.; Adeyemo, W.L.; Eshete, M.; Mossey, P.A.; Busch, T.; Aregbesola, B.; Donkor, P.; Arthur, F.K.N.; Bello, S.A.; Martinez, A.; Li, M.; Augustine-Akpan, E.A.; et al.
Orofacial clefts (OFCs) are congenital dysmorphologies of the human face and oral cavity, with a global incidence of 1 per 700 live births. These anomalies exhibit a multifactorial pattern of inheritance, with genetic and environmental factors both playing crucial roles. Many loci have been implicated in the etiology of nonsyndromic cleft lip with or without cleft palate (NSCL/P) in populations of Asian and European ancestries, through genome-wide association studies and candidate gene studies. However, few populations of African descent have been studied to date. Here, the authors show evidence of an association of some loci with NSCL/P and nonsyndromic cleft palate only (NSCPO) in cohorts from Africa (Ghana, Ethiopia, and Nigeria). The authors genotyped 48 single-nucleotide polymorphisms that were selected from previous genome-wide association studies and candidate gene studies. These markers were successfully genotyped on 701 NSCL/P and 163 NSCPO cases, 1, 070 unaffected relatives, and 1, 078 unrelated controls. The authors also directly sequenced 7 genes in 184 nonsyndromic OFC (NSOFC) cases and 96 controls from Ghana. Population-specific associations were observed in the case-control analyses of the subpopulations, with West African subpopulations (Ghana and Nigeria) showing a similar pattern of associations. In meta-analyses of the case-control cohort, PAX7 (rs742071, P = 5.10 × 10 −3 ), 8q24 (rs987525, P = 1.22 × 10 −3 ), and VAX1 (rs7078160, P = 0.04) were nominally associated with NSCL/P, and MSX1 (rs115200552, P = 0.01), TULP4 (rs651333, P = 0.04), CRISPLD2 (rs4783099, P = 0.02), and NOG1 (rs17760296, P = 0.04) were nominally associated with NSCPO. Moreover, 7 loci exhibited evidence of threshold overtransmission in NSOFC cases through the transmission disequilibrium test and through analyses of the family-based association for disease traits. Through DNA sequencing, the authors also identified 2 novel, rare, potentially pathogenic variants (p.Asn323Asp and p.Lys426IlefsTer6) in ARHGAP29 . In conclusion, the authors have shown evidence for the association of many loci with NSCL/P and NSCPO. To the best of this knowledge, this study is the first to demonstrate any of these association signals in any African population.